2007
DOI: 10.1017/s0007114507657869
|View full text |Cite
|
Sign up to set email alerts
|

Soluble dietary fibre fraction ofTrigonella foenum-graecum(fenugreek) seed improves glucose homeostasis in animal models of type 1 and type 2 diabetes by delaying carbohydrate digestion and absorption, and enhancing insulin action

Abstract: Trigonella foenum-graecum (fenugreek) seeds have been documented as a traditional plant treatment for diabetes. In the present study, the antidiabetic properties of a soluble dietary fibre (SDF) fraction of T. foenum-graecum were evaluated. Administration of SDF fraction (0·5 g/kg body weight) to normal, type 1 or type 2 diabetic rats significantly improved oral glucose tolerance. Total remaining unabsorbed sucrose in the gastrointestinal tract of non-diabetic and type 2 diabetic rats, following oral sucrose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(147 citation statements)
references
References 42 publications
2
144
0
1
Order By: Relevance
“…Several longer term clinical trials have also shown that administration of fenugreek seeds reduces fasting and post-prandial glucose levels and decreases glycated hemoglobin (33). Soluble fiber (45,46), saponins (47), trigonelline (48), diosgenin (49), and 4-hydroxyisoleucine (50) from fenugreek seeds have been suggested to mediate its hypoglycemic effect (33). The exact molecular targets and mechanisms remain unknown; however, N55 from fenugreek may potentially play a role in ameliorating glucose excursion in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Several longer term clinical trials have also shown that administration of fenugreek seeds reduces fasting and post-prandial glucose levels and decreases glycated hemoglobin (33). Soluble fiber (45,46), saponins (47), trigonelline (48), diosgenin (49), and 4-hydroxyisoleucine (50) from fenugreek seeds have been suggested to mediate its hypoglycemic effect (33). The exact molecular targets and mechanisms remain unknown; however, N55 from fenugreek may potentially play a role in ameliorating glucose excursion in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is characterized by body weight gain due to an increase in numbers and sizes of adipocytes (Karpovets et al, 2014;Konopelnyuk et al, 2015). Thus, it is important to reduce body weight and body fat to prevent obesity, and the increase in body fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the viscous fiber from fenugreek may have played a role in promoting satiety by slowing the rates of gastric emptying. Fenugreek galactomannan has been shown to slow gastric emptying in animal models (Hannan et al, 2007).…”
Section: Parametersmentioning
confidence: 99%
“…Fenugreek is widely used as a supplementary treatment for diabetes [10,11]. It causes dose-dependent reduction in blood glucose in normal and diabetic rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have shown that fenugreek causes reduction in blood glucose in type-1 and type diabetes-2 [10,13]. Preliminary reports suggested possible hypoglycemic effect of fenugreek seeds are related to high fiber content, high viscosity, inhibition of intestinal glycosidase activity [14], inhibition of glucagon release, increase in sensitivity to insulin [15], increase glucose-induced insulin secretion [16,17], potentiating insulin action [18], and inhibiting intestinal carbohydrate digestion and absorption [11]. Although, the anti-hyperglycemic effect of fenugreek has been shown in animal and human studies, the reports published so far on the hypoglycemic effect of fenugreek could not establish a direct relationship with glucose metabolism in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%